Calibrating adsorptive and reactive losses of monoterpenes and sesquiterpenes in dynamic chambers using deuterated surrogates - J. Zeng; J. Zeng; Y. Zhang; Y. Zhang; H. Ran; H. Ran; W. Pang; W. Pang; H. Guo; Z. Mu; W. Song; X. Wang; et al. (Atmospheric Measurement Techniques)
Accurately measuring the emissions of monoterpenes (MTs) and sesquiterpenes (SQTs) using dynamic chambers requires careful consideration of their adsorptive and reactive losses, which are often overlooked and difficult to assess in situ. This study evaluated the effectiveness of deuterated surrogates, α-pinene-d3 and β-caryophyllene-d2, in tracing these losses in a dynamic chamber system. Using standard gas mixtures of 10 MTs and 10 SQTs, we characterized adsorptive losses across varying concentrations, temperatures, and humidity levels, as well as reactive losses with ozone. Results indicated that adsorptive losses were significantly influenced by concentration and temperature, with species-specific variations particularly under low concentrations and low temperatures, while relative humidity had negligible impact. Reactive losses with ozone exhibited substantial species-specific variability. Key MTs (α-pinene, β-pinene, 3-carene, limonene, and 1,8-cineole) and SQTs (β-caryophyllene and α-humulene) demonstrated consistent adsorptive and reactive behaviors with their respective deuterated surrogates α-pinene-d3 and β-caryophyllene-d2, suggesting that these surrogates are effective for correcting losses with in situ emission measurements using dynamic chambers. However, due to varied adsorptive and reactive losses, additional deuterated MTs and SQTs are recommended, particularly selected according to their O3 reactivities, to cover a broader range of MTs and SQTs for loss correction. A strong correlation between adsorptive capacity and ozone reactivity was observed, underscoring the need to carefully address losses of highly reactive MTs and SQTs during emission measurements. This study also emphasizes that ozone-free circulating air should be used for accurately measuring emissions of highly reactive SQTs, such as β-caryophyllene and α-humulene, especially when loss correction methods are unavailable.